2002
DOI: 10.1210/jc.2001-010872
|View full text |Cite
|
Sign up to set email alerts
|

Altered Responsiveness of the Hypothalamus-Pituitary-Adrenal Axis and the Sympathetic Adrenomedullary System to Stress in Patients with Atopic Dermatitis

Abstract: A growing number of animal data strongly suggest that a hyporeactive hypothalamus-pituitary adrenal (HPA) axis may be pathologically significant by increasing the susceptibility to chronic inflammation. Following this line of evidence, the specific goal of the present study was to investigate the HPA axis in patients with atopic dermatitis (AD), a chronic allergic inflammatory disease. In addition, the sympathetic adrenomedullary (SAM) system as a second potent immunoregulatory and anti-inflammatory stress-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
148
2
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(165 citation statements)
references
References 45 publications
10
148
2
5
Order By: Relevance
“…On the other hand, close similarities between allergy and anxiety were documented [8,19,20]. Similar findings in allergy and anxiety were also found in HPA axis reaction to stress, where both allergy and high trait anxiety subjects exhibited lowered cortisol responses [5,26]. In light of these results, we hypothesize, that both allergy and high trait anxiety subjects exhibit an autonomic dysregulation, which can demonstrate itself in the form of hyperreaction or hyporeaction similarly to cortisol reactivity.…”
Section: Subjective Stress Differencessupporting
confidence: 68%
See 2 more Smart Citations
“…On the other hand, close similarities between allergy and anxiety were documented [8,19,20]. Similar findings in allergy and anxiety were also found in HPA axis reaction to stress, where both allergy and high trait anxiety subjects exhibited lowered cortisol responses [5,26]. In light of these results, we hypothesize, that both allergy and high trait anxiety subjects exhibit an autonomic dysregulation, which can demonstrate itself in the form of hyperreaction or hyporeaction similarly to cortisol reactivity.…”
Section: Subjective Stress Differencessupporting
confidence: 68%
“…Allostatic load can result in various dysregulations of allostatic systems, nervous, endocrine and immune system. Studies of neuroendocrine HPA (hypothalamus-pituitary-adrenal) axis in allergy [1,5] found lowered levels of salivary cortisol in response to psychosocial stress in patients with AD [5] and AR [1,6]. One of possible mechanisms of hypocortisolism is it being a result of chronic activation of HPA axis and, therefore, its inhibition through feedback regulation [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ezzel szemben a SAM-tengely két végterméke (adrenalin, noradrenalin) egyaránt erős immunaktiváló hatású [45,46,47,48]. Bár a fentiek ismeretében gyakori, krónikus stressz esetén magas kortizolszintet és csökkent immunműkö-dést várnánk, sok stresszkapcsolt betegségben (például rheumatoid arthritis, irritábilis bél szindróma, krónikus fáradtság szindróma, poszttraumás stressz zavar, fi bromyalgia) ennek pont az ellenkezőjét -normális vagy csökkent kortizolszinteket, túlzott immunaktivációt és autodestrukciót -fi gyelték meg [49,50,51,52]. A most bemutatni tervezett kutatási eredmények egy része pikkelysömör esetében is hasonló megfi gyeléseket tett, és a legfrissebb közlemények szinte kivétel nélkül megemlítik a diszfunkcionális HPA-tengely-működést, mint a pikkelysömörben jelentkező gyulladásos folyamat hátteré-ben meghúzódó egyik potenciális patomechanizmust.…”
Section: A Hypothalamo-hypophyseo-adrenalis éS a Sympathyco-adrenomedunclassified
“…Hypersecretion of cortisol across the day has been linked to the metabolic syndrome (Rosmond, 2005), immunologic decline (Elenkov, 2004), the development of mood disorders (Gold et al, 1998) and cognitive dysfunction (Lupien et al, 1998). In contrast, diurnal hyposecretion has been associated with increased risk of the development of autoimmune disorders such as rheumatoid arthritis (Masi & Chrousos, 1996), Sjögren's syndrome (Johnson et al, 1998) and dermatitis (Buske-Kirschbaum et al, 2002).…”
Section: Introductionmentioning
confidence: 99%